Identification of Pfdhfr mutant variants in plasmodium berghei model - Tipsuwan W. (2014)
Parasite resistance to antimalarials is a major burden in controlling malaria disease. Genetic mutations within the parasites are found to be the factor in conferring resistance to drugs. In this study, the power of random mutant library and transgenic parasite systems were employed to identify mutations on the antimalarial drug target, viz. Plasmodium falciparum dihydrofolate reductase (DHFR), which could contribute to resistance, and to elucidate the functionality of resistant mutant parasites in P. berghei. Using the moderate drug-resistant PfdhfrS108N gene as template, we generated a library of Pfdhfr mutants by error-prone PCR followed by transfection and selection in P. berghei. Two clones of transgenic P. berghei expressing PfDHFR of interest due to the position of mutations, i.e. PbPfDHFR3m1 (M55I+S108N+S189C) and PbPfDHFR3m2 (C50Y+S108N+F116S), were selected for drug sensitivity test. Although these transgenic parasite clones showed similar reproducibility with the parental transgenic P. berghei, expressing PfDHFR with mutation at S108N (PbPfS108N) in response to antifolate pyrimethamine, this study reconfirms that this P. berghei model is effective in predicting the evolution of Pfdhfr mutations in vivo. This approach can be applied during the development of new antifolates with better effective properties against drug resistant parasites. © 2011 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.